Construction and validation of a necroptosis-related lncRNA signature for predicting the prognosis of gastrointestinal cancer patients - Huang, Weicheng; Liu, Yuchen; Liu, Ruyi; Feng, Chi; Wu, Jiehua; Sun, Xing; Zhu, Pengfei; Chen, Pengxiang; Cheng, Yufeng (Frontiers in Immunology, 2025)
BackgroundGiven the high incidence and mortality rates of gastrointestinal (GI) cancer, along with the lack of effective prognostic markers, this study aimed to construct a prognostic signature to identify high-risk patients facilitate precision medicine, and ultimately improve patient outcomes.MethodsWe analyzed transcriptomic data for COAD, ESCA, READ, and STAD from the TCGA and GTEx databases. Using co-expression analysis, Cox regression, and least absolute shrinkage and selection operator (LASSO) regression, we developed a necroptosis-related lncRNA signature, termed the Necro-lnc score. The predictive performance of the score was validated and assessed through survival analysis, receiver operating characteristic (ROC) analysis, and Cox regression analysis. Additionally, we conducted gene set enrichment analysis (GSEA), immune landscape profiling, and drug sensitivity prediction based on half-maximal inhibitory concentration (IC50) values. The robustness of the score was further supported by cluster analysis, and the biological functions of the selected lncRNAs were experimentally validated through phenotypic assays.ResultsWe constructed a prognostic signature comprising five necroptosis-related lncRNAs, referred to as the Necro-lnc score. Calibration plots and areas under the ROC curves (AUCs) confirmed the strong prognostic predictive capability of the score. Kaplan-Meier (K-M) survival curves revealed a significant correlation between the Necro-lnc score and patient outcomes, with high-score patients exhibiting markedly poorer prognoses. Immune landscape and drug susceptibility analyses indicated that the high-score group was characterized by hot tumors and showed greater sensitivity to immunotherapeutic drugs and targeted drugs, while the low-score group associated with cold tumors, was more responsive to chemotherapeutic agents. Furthermore, in vitro phenotypic assays demonstrated that the lncRNAs included in the Necro-lnc score play critical roles in the progression and metastasis of GI cancer.ConclusionThis study developed the promising Necro-lnc score, which demonstrates potential for predicting prognosis and distinguishing between cold and hot tumors, thereby improving personalized treatment strategies for patients with GI cancer.